2010
DOI: 10.1585/pfr.5.s1019
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Entropy Analysis of the 2D Density Turbulence Measured by MIR in TPE-RX

Abstract: Two-dimensional (2D) turbulence measurement by using microwave imaging reflectometry (MIR) has been performed in the reversed field pinch (RFP) plasma in TPE-RX. In this work, the maximum entropy method (MEM) is used to estimate the 2D k-spectrum. The turbulences between the pulsed poloidal current drive (PPCD) and the high Θ plasmas are studied. The m = 1 modes are dominant in PPCD plasma, while in high Θ plasma the k spectrum expands to the high k range and the turbulence propagates in the electron drift dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The complex amplitude signals obtained from different positions can be used to deduce the 3D propagation structures in various fluctuations and instabilities via correlational analysis. 18 As in other reflectometry or interfer- ometry systems, the coherency of the illuminating and LO waves is indispensable in detecting the phase of the reflected wave. In addition, oscillator stability is important since the relative phases between different channels must be kept constant, at least during the timescale of the correlational analysis ͑e.g., Fourier transformation͒.…”
Section: Introductionmentioning
confidence: 99%
“…The complex amplitude signals obtained from different positions can be used to deduce the 3D propagation structures in various fluctuations and instabilities via correlational analysis. 18 As in other reflectometry or interfer- ometry systems, the coherency of the illuminating and LO waves is indispensable in detecting the phase of the reflected wave. In addition, oscillator stability is important since the relative phases between different channels must be kept constant, at least during the timescale of the correlational analysis ͑e.g., Fourier transformation͒.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulation and the laboratory test, we found that the phase / corresponds to the displacement of the cutoff surface in the radial direction and the amplitude A corresponds to the shape of the cutoff surface. 15 The amplitude A and phase / are detected by an RF detector and a quadrature detector, respectively. The quadrature detector provides the in-phase (I $ cos/) and quadrature (Q $ sin /) signals.…”
mentioning
confidence: 99%
“…These spectra are obtained by using the 2D maximum entropy method (MEM). 18,19 In the PPCD plasma, the fluctuation power is localized in the low k h and low k u range as k h ¼ 0 6 20 m À 1 , k u ¼ 0 6 10 m À 1 . The spectrum of the conventional RFP plasma distributes in a wide k range, as k h ¼ À 20 $ 20 m À 1 and k u ¼ À 40 $ 20 m À 1 .…”
mentioning
confidence: 99%
See 2 more Smart Citations